Development of TTG, Home Creative Industry and Digital Marketing in the Framework of Bamboo Processed Product Innovation - Tyasari, Irma; Susanti, Romia Hari; Susanto, Gaguk; FO, Eka Aprilia; Palupi, Andini Rida; Azzahra, Salsabila (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The purpose of PKM activities is to help increase production capacity and quality through technology transfer, home creative industry mindset and improve the managerial ability of IRT Pring Makmur, including digital marketing in the context of innovating processed bamboo products. The main issue of IRT is the problem of production processes that are still semi-manual and still use traditional business approaches. These limitations cause IRT to be unable to meet market demand and business development is less than optimal. Method: The service method applied is a combination of mentoring, consulting and training techniques by offering micro business integrative solutions. Practical Applications: Micro business integrative solution includes TTG Development which is carried out including the provision of production equipment assistance in the form of dynamo cutting machines, training on growing home creative industry concepts, digital marketing training and several other needed training. Conclusion: This PKM activity has resulted in gradual changes, both in aspects of production, creativity and product innovation, marketing methods, product packaging, management and recording of financial transactions and HR management.